(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: In recent years, one of the most pervasive issues regarding global public health is bacterial foodborne diseases Materials and Methods: A total of 164 different food samples were collected from September 2023 to November 2023 from a range of supermarkets and farmers throughout different locations in Babylon City. Milk products77 (52.70% ), meat products19(13%), seeds32(21.90%)and , canned 18(12.32%) . then culture in blood agar, chromogenic agar and not growth on macConkey agar, The virulence gene was amplified via the polymerase chain reaction (PCR). Results: The prevalence of Bacillus spp. , according to the cultured, biochemical, and molecular identification was 17(10.3%). The result of sequencing found the Bacillus spp. Isolates belong to the flowing species B.subtilis (2), B.cereus (6), B.thuringiensis(1), B.anthracis (1), B.spizizenii (1) and, Bacillus spp. (6). The result of molecular detection of virulence gene present hblA, nheA, and entFM in prevalence 4(23.5),11(64.7) , and 14(82.3) respectively Conclusion: The isolates of Bacillus spp. exhibited a variety of virulence factors correlated with symptoms of diarrhea. As a result, it is imperative to tightly enforce sanitary practices and pay more attention while processing food, adding chemicals only from reliable sources.